The Logic of Salvation in the Gospel of John - Kern, Daniel R. (Philosophy & theology, 2015)
I evaluate two claims; that (a) Jesus’s message as recorded in the gospels implies exclusivism with respect to salvation and that, correspondingly, (b) Christians should be exclusivists with respect to salvation. I evaluate these claims through a cataloguing and evaluation of the logical condition involved in each of the claims regarding conditions for salvation made by Jesus in the Gospel of John. As a result, I argue that (a) is false and that, correspondingly, so is (b).